Observing postprandial bowel movements in diaper-dependent toddlers. (20th October 2019) - Van Aggelpoel, Tinne; De Wachter, Stefan; Neels, Hedwig; Vermandel, Alexandra
The gastrocolic reflex is a response of the colon to the presence of food in the stomach. Our goal was to observe bowel movements in healthy infants and toddlers not yet toilet trained, in response to a meal. Stool behavior of 40 toddlers, aged 18–27 months, was monitored. We observed a bowel movement within the first hour after a meal in 75% of the children. This occurred 15, 30 or 60 minutes after a meal in, respectively, 25%, 48% and 66% of the observations. If we limit to the ones that actually defecated, 37% would defecate within 15 minutes and 72% within half an hour. Fifty-nine percent of all children defecated in the morning, 54% at noon and 28% in the evening. In conclusion, we believe the gastrocolic reflex can be used as a facilitating factor to help a child to defecate on the potty, 15–30 minutes after a meal. In 50% of the cases, a child will have a bowel movement on the potty and learn to defecate on it much easier.